Pathways to peace: Nonviolent communication restorative justice practices to enhance of socioemotional skills (Simbiótica. Revista Eletrônica, 2023)
This article addresses socioemotional education and the uses of Restorative Justice (RJ) and Non-Violent Communication (NVC) practices at School. The research carried out aimed to investigate how teachers in the early years of Elementary School can help students to use NVC and RJ practices in their relationships and contribute to the enhance the socioemotional educational process. Action-research was the methodological choice that made possible to investigate conceptions and practices of teachers in the early years of Elementary School at the XXX XXX State School, also carrying out continuing education of teachers. The intervention proposed to elucidate concepts of RJ, NVC and Socio-Emotional Education in the school context, proposing the creation of instruments for the experience of restorative practices.